The End of Myths. A fantastic Story in Sixteen Scenes - Stoyanov, Tzvetan (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2025)
Ironic prose from 1959–1960. First part of two scenes written by Tzvetan Stoyanov about the “sunset of the ancient gods under socialism”, where the “Olympians” have to be forcibly incorporated into a labor-production cooperative (LPC). An allusion to the fate of “foreign people” under “people’s power”, preceding the essay “Orpheus. Fooling around with mythology” (1963). Typescript from Tzvetan Todorov’s private archive kept by © Toni Nikolov. Published for the first time.